POTRET HEGEMONI KEKUASAAN DALAM NOVEL KERETA SEMAR LEMBU KARYA ZAKY YAMANI - Rahmawati, Puji; Wicaksono, Helmi (BASINDO : jurnal kajian bahasa, sastra Indonesia, dan pembelajarannya, 2023)
This research aims to analyze the form of hegemony of power and its influence in the novel Kereta Semar Lembu by Zaky Yamani based on Antonio Gramsci's Hegemony theory. The method used in this research is descriptive qualitative with a literary sociology approach. Hegemony of power becomes a concept that provides a portrait or description of the dominance or influence of power that results in social inequality and different groupings of social structures in society. The grouping is divided into groups of people with the highest strata to the lowest strata based on certain dimensions or benchmarks. The results of the analysis in this study show that there are forms of power domination and ideological influence in the novel.